The Cordon del Portillo Permian magmatism, Mendoza, Argentina, plutonic and volcanic sequences at the western margin of Gondwana - Gregori, Daniel Alfredo (2013)
The Cerro Punta Blanca, Cerro Bayo and Cerro Punta Negra stocks, parts of the Cordillera Frontal Composite Batholith, cropping out in the Cordón del Portillo, records the Gondwana magmatic development of the Cordillera Frontal of Mendoza, in western Argentina. In this area, the San Rafael Orogenic phase, that represents the closure of the Late Carboniferous-Early Permian marine basins, begins at 284 Ma, and ceased before 276 Ma. The Cerro Punta Blanca, Cerro Bayo and Cerro Punta Negra stocks represent a post-orogenic magmatism and are equivalents to the Choiyoi Group. The Gondwana magmatic activity in the Cordón del Portillo area can be divided into two stages. The Cerro Punta Blanca stock (c.a. 276 Ma) represents an early post-orogenic, subduction-related magmatism similar to the basic-intermediate section of the Choiyoi Group (c.a. 277 Ma). The late post-orogenic second event was recorded by the Cerro Bayo (262 Ma) and Cerro Punta Negra stocks which represent a transition between subduction-related and intra-plate magmatism. This event represents the intrusive counterpart of the acidic facies of the upper section of the Choiyoi Group (c.a. 273 Ma). This extensional condition continued during the Triassic when the Cacheuta basin developed.